Literature Review: Factors affecting the implementation of Early Initiation of Breastfeeding (EIBF) in maternity and breastfeeding mothers - Nur Aziza Wahdaliya; Ni'mal Baroya; Devi Arine Kusumawardani (Alma Ata University Press, 2023)
Background: Early initiation of breastfeeding (EIBF) is the process of direct skin contact between the mother and the baby within the first hour after delivery. EIBF affects the welfare and survival of newborns. Implementation of early breastfeeding initiation globally according to WHO is 42% and the low implementation of EIBF is influenced by several factors. Objectives: To identify factors that influence the implementation of Early Breastfeeding Initiation (EIBF) in mothers who give birth and breastfeed based on empirical studies in the last five years. Methods: The research method in this study was a literature review with the type of narrative literature review by using flowcharts to determine screening studies that were adjusted to the research objectives. A search for literature reference sources was carried out from August 2021 to March 2022 with secondary data. Research reference sources are 31 international articles using 3 databases, namely PubMed, Sciencedirect, and Springer. Results: The results of the study show that the mother's knowledge can be influenced by the availability of EIBF information, and the level of education of the mother. Parity has an influence on EIBF, because it is related to the mother's experience of breastfeeding. In caesarean delivery, it is influenced by post-delivery factors such as caesarean incision pain, the effect of anesthesia, and the mother's perception of milk production, whereas in normal delivery there are conditions of the mother's health that can affect the implementation of EIBF. Social support (husband, family and health workers) can encourage mother's confidence in the implementation of EIBF. Conclusions: There are several factors that influence and relate to the mother's knowledge, parity, type of delivery, social support, and health services on the success of EIBF in the implementation of EIBF in labor and breastfeeding mothers.